Treatment of domestic wastewater using activated carbon prepared from sugarcane bagasse - Del Angel, Ebelia; Pantoja, Mayra Agustina; López, Rosendo; Cruz, Alida Elizabeth (Tecnología y ciencias del agua, 2022)
Solid residues of sugar cane industry represent one of the major agro-residues. They are often considered as waste; however, they can be used as an inexpensive raw material for different applications, including production of activated carbon (CA) to be used as adsorbent in sustainable processes. On the other hand, domestic wastewater contains grease and oil residues, which causes pipe plugging. Adsorption of these compounds is possible with activated carbon. In this work, CA was obtained from sugarcane bagasse residues through a simplified two steps method: chemical activation with H3PO4 and pyrolysis at 973 K. Textural and structural characterizations were performed by N2 physisorption, scanning electron microscopy (SEM) and X-ray diffraction (XRD). Carbon samples (SBET = 914 m2g-1) showed a structure analogous to graphite and microporous surface characteristics of activated carbon. The adsorption of oils from domestic wastewater was evaluated with the synthesized carbon. Results showed that after eight hours, the sugarcane bagasse activated carbon adsorbed 94 % of the oils contained in wastewater. These data are similar to the adsorption process carried out in a commercial activated carbon (96 %). In this work also adsorption kinetics were evaluated with pseudo first-order, pseudo second order, and intraparticle equations, the experimental data showed a better fit with the pseudo second order model and to the Langmuir isotherm. These results prove the fact we can add value to sugarcane bagasse residues to efficiently remove greases and oils from wastewater.